2006
DOI: 10.1007/bf03033242
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia as an inflammation-mediated dysbalance of glutamatergic neurotransmission

Abstract: This overview tries to bridge the gap between psychoneuroimmunological findings and recent results from pharmacological, neurochemical and genetic studies in schizophrenia. Schizophrenia is a disorder of dopaminergic neurotransmission, but modulation of the dopaminergic system by glutamatergic neurotransmission seems to play a key role. This view is supported by genetic findings of the neuregulin- and dysbindin genes, which have functional impact on the glutamatergic system. Glutamatergic hypofunction, however… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
126
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(138 citation statements)
references
References 204 publications
(181 reference statements)
5
126
1
2
Order By: Relevance
“…However, studies using cultured microglial cells have shown effects of activation and production of inflammatory mediators in response to these cytokines (36)(37)(38). In addition, there is compelling evidence indicating that these cytokines may be involved in the neuropathology of schizophrenia (39,40). The present study showing increased levels of IL-4 and IL-13 transcription in the orbitofrontal cortex of suicides suggests that these cytokines may affect neurobehavioral processes relevant to suicide.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…However, studies using cultured microglial cells have shown effects of activation and production of inflammatory mediators in response to these cytokines (36)(37)(38). In addition, there is compelling evidence indicating that these cytokines may be involved in the neuropathology of schizophrenia (39,40). The present study showing increased levels of IL-4 and IL-13 transcription in the orbitofrontal cortex of suicides suggests that these cytokines may affect neurobehavioral processes relevant to suicide.…”
Section: Discussionmentioning
confidence: 61%
“…The latter relates to the activation or inhibition of the IDO enzyme that will ultimately result in altered serotonin metabolism and production of neuroactive substances. For reviews on these issues see (39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…Some novel approaches in medicine and psychiatry do not radically depart from assumptions embedded in the orthodox views of conventional biomedicine. For example psychoneuroimmunology (PNI) is a synthetic model that starts from established theories in psychiatry and biomedicine and postulates complex www.intechopen.com dynamic relationships between stress, immunological status and psychiatric or neurological symptom formation Muller & Schwarz 2007;Muller & Schwarz 2006). There is a rich discussion of PNI and other emerging paradigms in the peer-reviewed journal literature including emerging models in physics, biology and information science describing structure-function relationships in complex living systems.…”
Section: Novel Paradigms Are Shaping the Future Of Medicine And Mentamentioning
confidence: 99%
“…Recent studies suggest that nonspecific over-activation of the immune system involving T-helper cells takes place in subgroups of persons with schizophrenia (Strous & Shoenfeld 2006). The immune-mediated dysregulation of both dopamine and glutamate neurotransmission has also been implicated in the pathogenesis of schizophrenia (Muller & Schwarz 2006). In response to these findings, anti-inflammatory and immune-modulating therapies are being investigated as future treatments for affective disorders and schizophrenia.…”
Section: Novel Paradigms Are Shaping the Future Of Medicine And Mentamentioning
confidence: 99%
“…Several neurotransmitter abnormalities such as the dopaminergic, glutamatergic (GLU), GABAergic (γ-aminobutyric acid) deficits play important roles in schizophrenia [19,20].…”
Section: Pathophysiological Changesmentioning
confidence: 99%